2015
DOI: 10.1186/s13071-015-1128-3
|View full text |Cite
|
Sign up to set email alerts
|

Ticks and associated pathogens collected from cats in Sicily and Calabria (Italy)

Abstract: BackgroundLimited information is available about the species of ticks infesting the cat and the pathogens that they harbor. The aims of the present study were to identify the species of ticks removed from cats living in Sicily and Calabria (Italy) and to detect DNA of vector-borne pathogens in the same ticks.FindingsMorphological identification of 132 adult ticks collected throughout the year from cats was carried out. Real-time PCRs for Hepatozoon felis, Piroplasmid, Ehrlichia/Anaplasma spp., Rickettsia spp.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 20 publications
1
35
2
Order By: Relevance
“…has already been reported [25]. Recent studies [26,27] found that ticks from a number of genera test positive for the presence of L. infantum DNA. Ticks collected in northern and central Italy from dogs and cats in areas endemic for visceral leishmaniosis were found to be positive for L. infantum DNA by PCR [26].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…has already been reported [25]. Recent studies [26,27] found that ticks from a number of genera test positive for the presence of L. infantum DNA. Ticks collected in northern and central Italy from dogs and cats in areas endemic for visceral leishmaniosis were found to be positive for L. infantum DNA by PCR [26].…”
Section: Discussionmentioning
confidence: 83%
“…Ticks collected in northern and central Italy from dogs and cats in areas endemic for visceral leishmaniosis were found to be positive for L. infantum DNA by PCR [26]. In a study conducted in southern Italy, 11 of 132 (8.3%) ticks of various species removed from stray and owned cats tested positive for L. infantum DNA by PCR analysis [27].…”
Section: Discussionmentioning
confidence: 99%
“…18S rRNAGACGATCAGATACCGTCGTAGTCCCAGAACCCAAAGACTTTGATTTCTCTC0.3[62] Bartonella spp.ITS1AGATGATGATCCCAAGCCTTCTGCCTCCGACCTCACGCTTATCA0.3Modified from [63, 64] Ehrlichia spp. ; Anaplasma spp.16S rRNAGCAAGCYTAACACATGCAAGTCGGGATTATACAGTATTACCCAYCATTTCTARTG0.5[65, 66] H. canis 18S rRNACTTACCGTGGCAGTGACGGTATTGTTATTTCTTGTTACTACCTCTCTCAAAC0.3[66]Hemotropic Mycoplasma spp.16S rRNAATGTTGCTTAATTCGATAATACACGAAAACRGGATTACTAGTGATTCCAACTTCAA0.3/0.5[65] Rickettsia spp.ITS2GCTCGATTGRTTTACTTTGCTGTGAGCATGCTATAACCACCAAGCTAGCAATAC0.5/0.3[62] Abbreviations : rRNA ribosomal ribonucleic acid, ITS internal transcribed spacer …”
Section: Methodsmentioning
confidence: 99%
“…Branch lengths represent the number of substitutions per site inferred according to the scale-bar. Asio otus F Great Britain [16] a , [27] Athene noctua F Spain, [15] Tyto alba N Portugal [11] Galliformes Alectoris chukar ND Cyprus [31] Alectoris rufa F(+) France, Italy [16] [27,32,36], [37] Genetta genetta F, M Spain, other European regions [16] g , [38] Herpestes ichneumon F, M Spain [38,39] Vectors and Vector-Borne Zoonotic Diseases 6 but the establishment of I. ventalloi populations was only confirmed in the Britain islands [23,24]. In Portugal, I. ventalloi was first identified in 1985, and since then, it has been described across the country mainly in littoral mainland areas and along with other moisture-demanding ticks, such as Haemaphysalis spp., Ixodes frontalis, I. ricinus [6-8, 10-12, 25].…”
Section: Phylogenetic Trees Based On 16s Rrna Sequences Obtained Frommentioning
confidence: 99%